2015
DOI: 10.1186/s12887-015-0412-x
|View full text |Cite
|
Sign up to set email alerts
|

Parent/caregiver health literacy among children with special health care needs: a systematic review of the literature

Abstract: BackgroundChildren with special health care needs (CSHCN) are children with medical or behavioral diagnoses that require services beyond those generally needed by pediatric populations. They account for a significant portion of pediatric health care expenditures and often have complicated treatment regiments. Health literacy has recently been recognized as a key indicator of quality chronic disease self-management and parental/caregiver health literacy of CSHCN is an understudied area. The purpose of this syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 34 publications
0
40
0
6
Order By: Relevance
“…Our review is similar to a previous systematic review on parental HL. 10 The present review clearly indicates that parents require effective skills to appropriately assess and prevent the exacerbation of their children's asthma symptoms. However, children's HL is yet to be completely understood.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our review is similar to a previous systematic review on parental HL. 10 The present review clearly indicates that parents require effective skills to appropriately assess and prevent the exacerbation of their children's asthma symptoms. However, children's HL is yet to be completely understood.…”
Section: Discussionmentioning
confidence: 85%
“…Increasing evidence emphasizes the role of HL among adults 7 and parents of children in asthma care quality and control 9,18 and has revealed that HL is a valuable indicator of the outcomes of health education and self-management programs. 10,11 However, the relationship between children's HL and asthma remains unclear. A systematic literature review (1980e2014) revealed several research gaps in the direct assessment of children's HL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study by Heath et al [14] on Australian adolescents revealed that families with low educational and socio-economic status, a family history of language/ literacy difficulty, and low phonological awareness in parents could lead to poor literacy outcomes in children. Studies by Keim-Malpass et al [15] and DeWalt and Hink [16] reported that children whose parents had low literacy often had worse health outcomes and these findings reaffirmed Manganello's view [12].…”
Section: Gaps In the Literature On Health Literacymentioning
confidence: 84%
“…Their conclusion: "Parental/caregiver health literacy is an understudied area." 23 Almost universal access to the Internet has brought previously unimagined kinds and amounts of information to families of CYSHCN, with wide variability in its quality and reliability. Access to the Internet has its benefits, including facilitating families' connections to professional and family resources and organizations of many kinds at many levels, and importantly, to other families in similar situations, many willing to share information, support, strategies, tips, and resources.…”
Section: Consumer Choice and Health Care Financing Literacymentioning
confidence: 99%